2019
DOI: 10.3390/w11020196
|View full text |Cite
|
Sign up to set email alerts
|

Oxazepam Alters the Behavior of Crayfish at Diluted Concentrations, Venlafaxine Does Not

Abstract: Pharmaceutically active compounds are only partially removed from wastewaters and hence may be major contaminants of freshwaters. Direct and indirect effects on aquatic organisms are reported at dilute concentrations. This study was focused on the possible effects of environmentally relevant concentrations (~1 µg L−1) of two psychoactive compounds on the behavior of freshwater crayfish. Experimental animals exposed to venlafaxine did not show any behavioral alteration. Crayfish exposed to the benzodiazepine ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This suggests the potential of metazachlor exposure to result in slower cue responses. Crayfish are heavily dependent on processing a wide spectrum of visual, chemical, and water-borne signals 51 with escape behaviour as an appropriate response. A delayed response to predator presence and slower locomotion can be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the potential of metazachlor exposure to result in slower cue responses. Crayfish are heavily dependent on processing a wide spectrum of visual, chemical, and water-borne signals 51 with escape behaviour as an appropriate response. A delayed response to predator presence and slower locomotion can be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Trace organic compounds (TrOCs) of anthropogenic origin occur in very low concentrations (µg L −1 to ng L −1 ) in freshwaters, but might exhibit ecotoxicological effects, such as endocrine disruption, oxidative stress, growth inhibition, or altered behavior, even in the ng L −1 range [140][141][142][143]. For the HZ, especially polar, and thus highly mobile and persistent or pseudo-persistent (continuous release in the environment) TrOCs, are of relevance.…”
Section: Retention and (Bio)transformation Of Trace Organic Compoundsmentioning
confidence: 99%
“…It has been reported in the literature that compounds with varying modes of action can result in significant effects being found for some compounds, while others have no impacts on behaviour. A study on crayfish reported a significant increase in activity following oxazepam exposure while no significant impacts were observed for venlafaxine [ 43 ]. Studies on Daphnia behaviour with multiple psychotropic compounds found that fluoxetine induced the most severe behavioural effects and impacted behaviours at the lowest concentrations compared to all other compounds tested [ 1 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Including serotonin, dopamine, epinephrine and GABA receptors [ 1 ], making it possible for psychotropic compounds to have effects on non-target organisms in the environment. From the research to date, there appears to be a trend of increased activity in crustaceans exposed to both anxiolytics and antidepressants including fluoxetine and oxazepam [ 22 , 30 , 43 , 65 ] in amphipod and decapod species. To date, the impact of psychotropic compounds on the swimming of anostraca species remains unexplored.…”
Section: Introductionmentioning
confidence: 99%